Exploratory Study of the Phenomenon Quiet Quitting: Manager’s Perspective in a Digital Company - Rahmadara, Belinda; Rachmawati, Riani (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2025)
Objective: This research aims to explore the phenomenon of "quiet quitting" in digital companies from managers' perspectives. It investigates the causes, behaviors, and impacts of quiet quitting and examines managerial strategies to mitigate this issue and its implications for employee engagement and organizational performance. Design/Methods/Approach: This qualitative exploratory study employed semi-structured interviews with managers from some digital companies. Participants were selected using the purposive and snowball sampling methods. Data were collected from September to November 2024 and analyzed using thematic analysis, guided by the Social Exchange Theory (SET) and the Job Demands-Resources (JD-R) Model. Findings: The findings reveal that quiet quitting is primarily triggered by insufficient recognition, poor communication, excessive workloads, and misalignment between employees’ values and organizational culture. Quiet quitting behaviors include minimal task completion, withdrawal from team activities, and reduced initiative. Effective leadership through transparent communication and recognition was found to mitigate this issue. Organizational strategies, such as flexible work arrangements, fair compensation, and career development opportunities, also effectively reduced the need to quit. However, this phenomenon negatively impacts team productivity, morale, and organizational reputation. Originality/Value: This study contributes to the literature by providing insights into quiet quitting within the country’s cultural and economic context. Unlike Western-centric studies, it incorporates local values such as collectivism and hierarchical structures, offering a culturally sensitive understanding of this phenomenon in the digital sector. Practical/Policy Implications: Managers who seek ways to improve employee engagement are advised to foster open communication, recognize employee contributions, and ensure fair workloads. Flexible work arrangements and opportunities for career development can enhance employee engagement and retention. Policymakers and HR practitioners should develop culturally adaptive strategies to address quiet quitting while promoting employee well-being.